Efektivitas Penanganan Konflik Sosial Oleh Tim Terpadu Di Provinsi Dki Jakarta - Anadirga, Cika Nurunnisa; Nurdin, Nurliah Nurdin; Sinurat, Marja (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
ABSTRACT Social conflict is a physical feud that occurs between two or more groups of people that lasts for a certain timeand has a wide impact that results in social insecurity so as to disrupt national stability and development. To address the social conflict, the Integrated Social Conflict Handling Team was formed. The purpose of this research is to analyze the effectiveness of the Integrated Team in handling social conflicts in the DKI Jakarta Province and to identify bettersolutions for the team to effectively manage social conflicts. This research is a qualitativ descriptive research using data collection techniques in the form of interviews, observations and documentation as well as triangulation data processing.The effectiveness of handling social conflicts by integrated teams is analyzed using the theory of effectiveness according to Steers (2002: 209), namely organizational characteristics, environmental characteristics, worker characteristics and management practices.This research result concludes that the integrated team for handling social conflicts in DKI Jakarta has not been effective yet. This is due to bureaucratic and partial coordination and synergy within the integrated team.The better solution is for the integrated team to thoroughly examine the problem starting from its root cause, organize the integrated team operationally, and raise public awareness in avoiding social conflict triggers. The writer's suggestion is that the government needs to not only consider the actors in social conflicts, but also examine the underlying processes that have been driving these events, as they are the deeper reasons that need further investigation.